LENGTH-WEIGHT RELATIONSHIP OF GOLDEN MAHSEER TOR PUTITORA (HAMILTON) FROM PONG DAM RESERVOIR, HIMACHAL PRADESH - JOHAL, M.S.; NEGI, R.K.; ONKAR, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2005)
Growth studied of Tor putitora (Ham.) using length-weight relationship was conducted on the specimens obtained from the Pong reservoir. The statistical relationship between length-weight of the fish was derived as suggested by parabolic equation by Lecren (1951). The value 'n' of length-weight relationship was 3.150, 3.313 and 2.958 from pooled, females and males specimens, respectively.